Design and Simulation of Rotary Dryer Frame Strenght using Finite Element Analysis - Lathifa Putri Afisna; Irfan Dafa Denara; Eko Pujiyulianto; Vicky F Sanjaya (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Cow dung drying machine is used to overcome problems in processing cow dung. The type of drying machine selected is a rotary dryer type which rotates a drum or cylinder to stir the object being dried. A strong framework is needed to support the components of the dryer so that in its manufacture a static load analysis is needed so that the frame can support the load it will receive. The purpose of this research is to design, simulate and analyse the maximum stress and displacement in the frame structure of the rotary dryer using the finite element method in Solidwork. The simulation results show that the maximum stress supported by the engine frame is 7.115×105N/m2 and the maximum displacement is 1.315×10-2mm. The maximum stress value obtained is smaller than the yield stress of the frame material. This value indicates that the design of the rotary dryer machine frame structure is safe to proceed to the production stage. Mesin pengering kotoran sapi digunakan untuk mengatasi masalah dalam pengolahan kotoran sapi. Jenis mesin pengering yang dipilih adalah tipe rotary dryer yang memutar drum atau silinder untuk mengaduk benda yang dikeringkan. Diperlukan kerangka yang kuat untuk menopang kompone-komponen mesin pengering sehingga dalam pembuatannya dibutuhkan analisis beban statis agar kerangka tersebut mampu menopang beban yang akan diterimanya. Tujuan penelitian ini adalah untuk mendesain, mensimulasi dan menganalisa tegangan maksimum serta displacement pada struktur rangka mesin rotary dryer dengan metode elemen hingga pada Solidwork. Hasil simulasi menunjukkan tegangan maksimum yang ditumpu rangka mesin sebesar 7,115×105